2021
DOI: 10.1007/s00508-021-01986-w
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive outcomes after bariatric surgery in women

Abstract: SummaryThe presence of obesity may significantly influence female fertility through various mechanisms. Impairment of the hypothalamic-pituitary-ovarian axis in obese women may induce anovulation and infertility. Obesity may have an effect on women’s spontaneous and assisted conception rates, increased miscarriage rates, premature labor, stillbirth and perinatal risks, and menstrual irregularity. It has been suggested that weight loss improves reproductive outcomes due to fertility amelioration and an improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…Bariatric surgery is an invasive procedure, and will cause a delay in fertility treatment because it is undesirable to conceive during a period of rapid weight loss. Furthermore, pregnancy complications due to nutrient malabsorption after bariatric surgery are also possible [ 1 , 38 ]. Other less invasive options, such as the use of insulin sensitizers like metformin or thiazolidinediones, are proven to be beneficial for weight loss and the treatment of infertility in women with PCOS [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bariatric surgery is an invasive procedure, and will cause a delay in fertility treatment because it is undesirable to conceive during a period of rapid weight loss. Furthermore, pregnancy complications due to nutrient malabsorption after bariatric surgery are also possible [ 1 , 38 ]. Other less invasive options, such as the use of insulin sensitizers like metformin or thiazolidinediones, are proven to be beneficial for weight loss and the treatment of infertility in women with PCOS [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This genomic region may be selected to improve the reproduction performance of Jinhua pigs. Obesity is closely related to reproduction and fertility, such as embryonic development ( 65 ) and spermatogenesis ( 66 ) through various mechanisms. Low BFT is an important breeding objective for Duroc pigs, and animals carrying this adverse ROH showed higher BFT values than Non-carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines from the American Association of Clinical Endocrinologists, The Obesity Society, and American Society for Metabolic and Bariatric Surgery recommend that pregnancy be delayed until 12 to 18 months postprocedure to allow for weight stabilization and then, when pregnant, optimal nutrition for fetal growth. 30 Fertility indicators improve 31 and women generally show an increase in sexual activity postsurgery. 32 However, a retrospective cohort study indicated that only around 55% of those who underwent bariatric surgery and were at risk of pregnancy had documented use of contraception postsurgery.…”
Section: Weight Managementmentioning
confidence: 99%